Beginning of the age of mammals in Asia : the late Paleocene Gashato fauna, Mongolia. Bulletin of the AMNH - Szalay, Frederick S.; McKenna, Malcolm C.; Central Asiatic Expeditions (1921-1930) (New York : [American Museum of Natural History], 1971)
p. 271-317 : ill., maps 27 cm. Includes bibliographical references (p. 314-317). "The earliest Tertiary mammalian fauna known from Asia occurs in southern Mongolia, where it is found in late Paleocene sediments approximately 55 million years old exposed at Gashato and in the Nemegt Basin. Romer (1966) has proposed, but not defined, a 'Gashatan Asiatic Age' for the Gashato fauna and we propose that the term be extended to the occurrence of the same fauna, although to a different faunal facies, in the Nemegt Basin, subsuming Romer's (1966) 'Ulanbulakian Asiatic Age.' We supply a definition of the 'Gashatan Asiatic Age': the joint overlapping time ranges of Palaeostylops, Pseudictops, Prionessus, and Eurymylus. Additional localities in Sinkiang and Kwangtung may also be Gashatan in age. The Gashato fauna is made up of a mixture of endemic genera and a few genera that evidently reached Asia via the Bering route from North America and beyond. There is no special similarity to Paleocene faunas of Europe, but this could be because of a double filtering action. Gashatan mammals have been the notoungulates, but recently Paleocene notoungulates been found in North America and there is no evidence that notoungulates as such originated in Asia. At the beginning of the Eocene (Sparnacian), increased northern dispersal brought about extensive, but still not complete, faunal replacement in eastern Asia. Analysis of geophysical data, as well as the faunal data, suggests that there is strong evidence for a dry-land dispersal route between the North American and European crustal blocks via Greenland and the Barents shelf as late as Sparnacian time in the Eocene, but not thereafter. During Paleocene time, climate and other factors had a filtering effect on dispersal via both the Bering and Greenland-Barents shelf routes, but the former was closer to the rotational pole position in the Paleocene and was a more effective filter. During Sparnacian time, the Bering area still acted as a filter, but the Greenland-Barents shelf ...